2005
DOI: 10.1002/pds.1190
|View full text |Cite
|
Sign up to set email alerts
|

Herbal products: behaviors and beliefs among Italian women

Abstract: The present survey highlights the general use of phytomedicines by a sample of Italian women, the potential risk of their confidence with the 'natural world,' and the lack of discussion on this argument with doctors and pharmacists. This suggests the importance of training for health care providers and the need of informational programs for consumers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
36
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 26 publications
8
36
2
1
Order By: Relevance
“…8 Upper respiratory tract infections (URIs) are among the leading reasons for doctor visits 9 and a common diagnosis in primary care. 10 A study by Jeschke et al (2007) of 12,081 outpatients in Germany found that 63.0% of patients with diseases of the respiratory system were treated with CAM drugs only.…”
mentioning
confidence: 99%
“…8 Upper respiratory tract infections (URIs) are among the leading reasons for doctor visits 9 and a common diagnosis in primary care. 10 A study by Jeschke et al (2007) of 12,081 outpatients in Germany found that 63.0% of patients with diseases of the respiratory system were treated with CAM drugs only.…”
mentioning
confidence: 99%
“…Besides, websites were also assessed how frequently they include the phrase "natural", which may seem descriptive and innocent at first glance since majority of weight loss supplements hold herbal ingredients. However, consumers may tend to perceive "natural" as "safe" [19], therefore this phrase, which was used by 76% of websites include in our study, may also be misleading for the average consumer.…”
Section: Discussionmentioning
confidence: 98%
“…Misleading statements like "100% safe", "No side effects" were present in 91% of the websites. Recent studies indicate that consumers often (44.7%-71.8%) take herbal drugs in combination with prescription drugs [19,20], and it is suggested that herb-drug interactions may also be significantly underreported, and accompanying the fact that monitoring the adverse effects of herbs and herb-drug interactions is not fully developed in many countries [21]. Since the majority of the available weight loss supplements include herbal ingredients, the awareness of the potential drug interactions is of great importance in daily clinical practice considering that patients may not perceive herbal supplements as drugs and they may ignore to inform their health care provider of their use [22].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other constituents of dandelion root water extract improved lipid metabolism and prevented diabetic complications from lipid peroxidation in diabetic rats (Cho et al, 2002). A preliminary report suggests that dandelion root reduces the recurrence rate of urinary tract infections in women (Zaffani et al, 2006) Products containing dandelion pollen can cause allergic reactions, including anaphylaxis when it is taken orally (McCutcheon et al, 2002). In one report, a 39-year-old obese woman developed palpitations and syncope after taking a weight loss supplement containing a combination of dandelion, bladderwrack, and boldo for 3 weeks.…”
Section: Dandelion (Taraxacum Officinale)mentioning
confidence: 99%